UPAYA GURU DALAM PENANAMAN NILAI TOLERANSI ANTAR UMAT BERAGAMA DALAM MATERI AQIDAH AKHLAK DI SEKOLAH NEGERI - Nur Zakiya; Muhammad As’ad Ali; Laila Badriyah (CV. ADIBA AISHA AMIRA, 2025)
An attitude of tolerance is the identity of the Indonesian state which is currently not doing well. It seems that everyday life is affected by the low standards of tolerance and social care in Indonesia. Tolerance in students' lives is decreasing, as is the case in the classroom. Many behaviors that encourage tolerance now appear negative in the eyes of the school community. In this research, the author uses a qualitative approach to better understand the reality of the events being studied and facilitate objective data collection, and the research also uses descriptive methods. This research describes how teachers make efforts to instill the value of tolerance between religious communities in moral aqidah material at school. The subjects in this research are students and teachers at SMAN 1 Waru, Sidoarjo. Thus it can be seen that aqidah akhlak is a real and structured effort in preparing pupils or students to know each other, understand each other, appreciate each other and have faith in God. Almighty One and apply it into a commendable moral attitude in everyday life based on the Al-Qur'an and Hadith, by going through a process of mentoring, giving lessons and exams